PENGARUH GCG, CSR, DAN LEVERAGE TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL MODERASI - Defri; Muhammad Rahmat; Silvia Rizli Basnawati; Mefri Yudi Wisra (LPPM Universitas Ibnu Sina, 2023)
This study aims to examine the effect of GCG, CSR, and Leverage on Firm Value with Profitability fas fa fmoderating fvariable. fThe fsample fused fin fthis fstudy fuses fmanufacturing fcompanies flisted fon fthe fIndonesia fStock fExchange f(IDX) fin fthe fperiod f2016 fto f2020. fThe fnumber fof fsamples fused fis f25 fcompanies fwith f125 fobservations. fThe fsample fmethod fused fin fthis fresearch fis fpurposive fsampling, fwhile fthe fdata fanalysis fmethod fused fis fpanel fdata fregression fusing fthe fSPSS fprogram. The fresults fof fthis fstudy findicate fthat fGCG fhas fa fpositive feffect fon ffirm fvalue, fCSR fhas fno fnegative feffect fon ffirm fvalue, fand fleverage fhas fa fpositive feffect fon ffirm fvalue. fMeanwhile, fprofitability fas fa fmoderating fvariable fweakens fGood fCorporate fGovernance fon ffirm fvalue